Edukasi Pemanfaatan Aloe vera Sebagai Bahan Alternatif Untuk Mengurangi Kandidiasis - Qurrohman, Muhammad Taufiq; Sitohang, Dahlan; Rizki, Andita Ainal; Shaleha, Annisa Azizah; Rasid, Bryan Aditya Nur; Sanita, Hanifah Velda; Annisa, Mariana Suryanti Nur; Maharani, Raras; Tambunan, Yohana Nathalia (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Candidiasis is an opportunistic fungal infection that frequently affects the skin, particularly among individuals with suboptimal personal hygiene and those living in humid environments. One natural substance that has the potential to inhibit the growth of Candida albicans is Aloe vera, which contains saponin and lupeol with antifungal activity through the mechanism of disrupting fungal cell membrane integrity. Based on this background, a community service program was conducted to enhance the knowledge and skills of residents in utilizing Aloe vera as a natural ingredient for the prevention of candidiasis. The activity took place in Bentakan Village, Baki District, Sukoharjo Regency, involving 18 women of productive age as participants. The method included a pre-test, interactive lecture, demonstration of Aloe vera soap production, post-test, and evaluation. The average pre-test score of 54.44 increased to 77.77 in the post-test, with the Wilcoxon test showing p < 0.05. This finding indicates a significant improvement in participants’ understanding of candidiasis prevention and promotes positive changes in personal hygiene behavior. The sustainability of this program is expected to be supported through follow-up training and the establishment of community empowerment groups as small-scale producers of herbal soap with economic value.